Features and outcome in meningococcal disease presenting with maculopapular rash. Issue 4 (April 1991) - Marzouk, O; Thomson, A P; Sills, J A; Hart, C A; Harris, F
Abstract : Sixty nine patients with meningococcal disease some of whom presented with a maculopapular rash were entered in a prospective multicentre study. The clinical and laboratory features of children presenting with maculopapular rashes were compared with those of children presenting with typical haemorrhagic rashes. Of the 69 children 26 (38%) developed maculopapular rashes; nine (13%) had a maculopapular rash only, and the remaining 17 had a mixed maculopapular-purpuric rash. Twelve of the 17 (7%) had less than 12 petechiae. Children with maculopapular rashes had significantly higher platelet counts (median 294 compared with 243 x 10(9)/l), and plasma total haemolytic complement activity (80.5 compared with 65.0 U/ml) and significantly lower Glasgow meningococcal septicaemia prognostic scores (2.5 compared with 5.5) than those with purpuric rashes on admission. There were no significant differences between the groups in mortality, white cell count or absolute neutrophil count on admission, or C reactive protein concentration. Meningococcal disease can present with a maculopapular rash alone but this does not necessarily mean that the disease is less severe.